Causes and consequences of temporomandibular disorders (Research, Society and Development, 2022)
The term temporomandibular disorders (TMD) encompasses several circumstances that affect the temporomandibular joint, the masticatory muscles or both. TMD can be painful and not painful. In addition to causing sensory discomfort, painful TMDs are emotionally disadvantageous, causing feelings such as anxiety, stress, guilt, misery, isolation and even difficulty sleeping, which can lead to the development of depression. For the construction of this work, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. TMD are a complex set of disorders that can often lead to chronic pain. As research advances are made, a greater understanding of the multifactorial etiology of painful TMD is developing. This will likely lead to the development of better TMD prevention, diagnosis, and treatment strategies that target individual mechanisms and contributing factors. A biopsychosocial framework of care is advised for the treatment of TMD, encompassing a multidisciplinary approach through a single integrated treatment pathway. Research suggests that establishing regional centers specializing in orofacial pain can provide a more streamlined and cost-effective management approach in secondary or tertiary care.